Cascade Structural Encoding of Binary Arrays - Barannik, Vlad.; Hahanova, A. V. (EWDTS, 2008)
The lacks of existent approaches come to light in relation to the compression of binary data for their use in digital diagnostics. It is grounded, that due to presentation of binary array as integral structure as a cascade structural number, satisfying limits on the number of carouses of units and on the dynamic range of cod-numbers of OFSN additional reduction of structural surplus is provided. The basic stages of binary of a two stage cascade structural encoding are expounded. Proved, that amount of digits on presentation of binary column examined as an element of cascade structural number less than, than amount of digits on presentation of that column, but examined as an onedimensional floating structural number. The features of treatment of diagnostic information consist of that: on treatment test sets, having an arbitrary structure and different statistical descriptions, are given; test information appears in a binary kind; the lead through of diagnostics of digital charts is carried out on the basis of the kept test sets. Digital diagnostics means related to the increase of volumes of test information. From here is the scientifically-applied task, consisting of diminishing of volumes of test information.
Keywords: Cascade Structural Encoding; Binary Arrays; digital diagnostics; OFSN